Nanostructured lipid carrier (NLC) in topical preparations: a narrative review of components, manufacturing methods, characteristics and activities - Rizikiyan, Yayan; Sugihartini, Nining; Rais, Ichwan Ridwan (Faculty of Pharmacy, Universitas Pancasila, 2025)
Nanostructured Lipid Carries NLCs have gained attention in formulation science and nanotechnology due to their biocompatible material and ability to enhance skin penetration. The goal is to create products that can effectively deliver active compounds to desired skin layers with minimal side effects. This review focuses on the use of functionalized NLCs in dermocosmetics, specifically looking at their composition, manufacturing method, characteristics, and role in delivering active compounds. The review obtained articles from databases such as Scopus, Pubmed, and Google Scholar, covering the years 2014-2024. Data search was conducted in May 2024. The search used keywords such as